Factors that influence pregnant women's adherence to consuming fe tablets - Idawati; novera, eka; husna, iswaton; wati, erna; marlisa, mira (International Journal on ObGyn and Health Sciences, 2023)
Pregnant women can be at risk for anemia, especially anemia due to iron deficiency. Anemia occurs due to low hemoglobin content in the body during pregnancy or less red blood cells in the blood than usual, with hemoglobin levels below 11 g%. The impact that can be caused by anemia in pregnant women is bleeding during childbirth, low birth weight babies (LBW), decreased IQ, babies are easily infected and easily suffer from malnutrition.